2021
DOI: 10.2147/ijgm.s317348
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Media on Public Health Awareness Concerning the Use of Natural Remedies Against the COVID-19 Outbreak in Saudi Arabia

Abstract: Background The coronavirus disease (COVID-19) pandemic has caused major health system problems and has fueled the emergence of various misinformation regarding preventive measures. The current study was conducted to evaluate the effect of media on raising the level of health awareness of Saudi Arabian populations regarding the medical misinformation about the use of natural remedies against COVID-19. Methods This descriptive cross-sectional study was conducted anonymous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 21 publications
3
33
0
Order By: Relevance
“…The apparently docile nature of COVID-19 related information recirculation in Saudi Arabian social media platforms is a positive indicator that the general population are aware of the necessary sources, such as the Ministry of Health in Saudi Arabia for getting their information. 36,37 However, consistent with the findings of other studies regarding judging the validity of information on social media platforms, the Saudi Arabian general population are more likely to judge the validity of information based on their own experience, and deem it beneficial for the public to share COVID-19 related information sans evidence. 10,[16][17][18][19][20][21] Thus, it can be posited that Saudi Arabian general population's perception of COVID-19 related information circulating on social media platforms is of a neutral disposition.…”
Section: Discussionsupporting
confidence: 67%
“…The apparently docile nature of COVID-19 related information recirculation in Saudi Arabian social media platforms is a positive indicator that the general population are aware of the necessary sources, such as the Ministry of Health in Saudi Arabia for getting their information. 36,37 However, consistent with the findings of other studies regarding judging the validity of information on social media platforms, the Saudi Arabian general population are more likely to judge the validity of information based on their own experience, and deem it beneficial for the public to share COVID-19 related information sans evidence. 10,[16][17][18][19][20][21] Thus, it can be posited that Saudi Arabian general population's perception of COVID-19 related information circulating on social media platforms is of a neutral disposition.…”
Section: Discussionsupporting
confidence: 67%
“…Our results as well as those of a study conducted in Saudi Arabia 16 showed that media was the main source of information from which more than 80% of the participants reported to have seen or accessed messages about herbal medication use. Media further increased the use of herbal medication in 65% of the participants which is consistent with what studies by Alotiby et al 14 and Alyami et al 4 reported that the biggest motivators for participants to pursue herbal products were Media and the Internet. 4 , 14 However, the majority of participants in our study reported that they would hold information from the Ministry of Health and WHO with high regard a finding consistent with that of Kwok et al 29 and Alotiby et al 14 In this respect, policymakers and health workers could use this opportunity to disseminate the right information to the public regarding the safe use of herbal remedies.…”
Section: Discussionsupporting
confidence: 87%
“…Media further increased the use of herbal medication in 65% of the participants which is consistent with what studies by Alotiby et al 14 and Alyami et al 4 reported that the biggest motivators for participants to pursue herbal products were Media and the Internet. 4,14 However, the majority of participants in our study reported that they would hold information from the Ministry of Health and WHO with high regard a finding consistent with that of Kwok et al 29 and Alotiby et al 14 In this respect, policymakers and health workers could use this opportunity to disseminate the right information to the public regarding the safe use of herbal remedies. 30 The current study revealed a mean FCV-19S score of 21.7 (SD=5.9, median=21).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Broadcasting positive news during the pandemic may bring behavioral changes in people (Shekhar, 2021). Media can improve public health, mental awareness, and bring good behavioral changes (Alotiby, 2021). Promoting more positive news regarding successful vaccinations camps -as well as highlighting interviews as regards standard operating procedures (SOP) of administering vaccines and assurances of monitoring the vaccination drives can boost public morale.…”
Section: Discussionmentioning
confidence: 99%